Efektivitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Kabupaten Klaten pada Bencana Banjir Melalui Strategi Card Sort Di SMA N 1 Klaten - Winarso, Okto Dwi, Drs. Dahroni, M.Si (2016)
SMA N 1 Klaten that addresses Jl .Merbabu no. 13 Gayamprit Southern District of Klaten district of Central Java province . The strategy used in classroom lessons heavily influence the study . Regional Disaster Management Agency disaster have a guide book in which there are materials about disasters. In this study using a strategy card sort for examine effectiveness of the instructional materials. Grading seen from the value of the average student in the mid repeat the semester , the highest as a class experiment. Control class in learning to use the conventional strategy , while the experimental class using the strategy card sort. Mechanical testing instruments used validity , reliability test. Data retrieval assessed Tertiary students with the knowledge about the calculation of pre-test and post test. Data were analyzed using normality test , homogeneity test and test hypotheses all used SPSS 21. The data obtained show that the gain control class The mean value of 70.0 while the experimental group gained an average value of 78.9. Pre test in this study scored Sig ( 2 - tailed) is greater than the probability value 0.137 > 0.05 then H0 class got Sig post test ( two - tailed lower than the probability value 0.03 < 0.05 H0. Test with paired simples type of test to demonstrate the value Sig ( 2 - tailed ) was lower than the 0.00 probability value > 0.05 then H0 is rejected. The conclusion that there was an increase learning outcomes through strategic card sort with teaching materials guide books disaster Klaten district in the floods in SMA N 1 Klaten. Keywords : Materials Handbook , Effectiveness